2019
DOI: 10.4103/aian.aian_444_18
|View full text |Cite
|
Sign up to set email alerts
|

Mineralizing angiopathy of lenticulostriate arteries with infantile basal ganglia infarct following minor head trauma: A case series

Abstract: Acute arterial ischemic stroke after minor head trauma has been reported in the past, mostly in infants. Most of these affected children had basal ganglia infarct on imaging. Investigations for other etiologies of stroke were noncontributory in most of the cases. Thin-slice computed tomography scan may show mineralizing angiopathy of lenticulostriate arteries. We report a clinical series of four infants who presented with the classical features of this distinct clinico-radiological entity. Clinical characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
1
7
2
Order By: Relevance
“…However, some studies have found that basal ganglia calcification is actually the manifestation of mineralizing angiopathy of lenticulostriate arteries [ 4 ]. In this study, 21/109 (18.3%) children had bilateral basal ganglia calcification, and the incidence was almost consistent with previous studies [ 13 , 16 ]. All patients underwent blood and urine metabolic screening to ensure that basal ganglia calcification caused by genetic metabolic diseases was excluded.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, some studies have found that basal ganglia calcification is actually the manifestation of mineralizing angiopathy of lenticulostriate arteries [ 4 ]. In this study, 21/109 (18.3%) children had bilateral basal ganglia calcification, and the incidence was almost consistent with previous studies [ 13 , 16 ]. All patients underwent blood and urine metabolic screening to ensure that basal ganglia calcification caused by genetic metabolic diseases was excluded.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the development of sphenoid bone in children is now complete; it cannot completely cover the temporal lobe, which makes the subarachnoid space relatively wide, consequently making the brain tissue and skull base more likely to undergo large horizontal displacement upon an acceleration or deceleration injury so that the lenticular artery is damaged [ 9 ]. A study reported that a child had an abnormal lenticular artery at the age of 1 month, and several months later, an ischaemic stroke was observed after mild trauma; at the same time, lenticulostriate artery mineralization was demonstrated [ 13 ]. Ivanov et al reported trauma-associated ischaemic stroke in an 8-month-old infant with pre-existing lenticulostriate vasculopathy [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]7 Hemiparesis is the most common symptom in this condition, followed by epileptic seizures. [1][2][3][7][8][9] Although this was not the case in this patient, a significant percentage of children with transient hemidystonia on the affected side has been reported. 1,7,9 At first, calcifications are asymptomatic, generally bilateral, multiple, and nonprogressive, which tend to disappear or decrease with age.…”
Section: Discussioncontrasting
confidence: 52%
“…[1][2][3][7][8][9] Although this was not the case in this patient, a significant percentage of children with transient hemidystonia on the affected side has been reported. 1,7,9 At first, calcifications are asymptomatic, generally bilateral, multiple, and nonprogressive, which tend to disappear or decrease with age. 1,2 These calcifications typically appear on the CT scan as linear hyperdense lesions that run vertically through the lentiform nucleus's inferior sector, mimicking the lenticulostriate arteries' anatomy.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation